Minocycline/Amoxicillin-Based Bismuth Quadruple Therapy for Helicobacter pylori Eradication: A Pilot Study - Senlin You; Xiaoqiong Tang; Jiarui Zhou; Yalin Shen; Xiaona Song; Mohammed Benghezal; Barry J. Marshall; Hong Tang; Hong Li (Microorganisms, 2024)
The common adverse effects and the complicated administration of tetracycline and metronidazole greatly affect the clinical application of the classical bismuth quadruple therapy (BQT) for Helicobacter pylori eradication. This pilot study aimed to evaluate the efficacy and safety of minocycline/amoxicillin-based BQT for H. pylori eradication. Firstly, consecutive H. pylori isolates collected at West China Hospital of Sichuan University between 2018 and 2021 were included for susceptibility testing of tetracycline and minocycline using E-test strips. Secondly, both treatment-naïve and experienced patients were included to receive a 14-day minocycline/amoxicillin-based BQT: esomeprazole 40 mg or vonoprazan 20 mg, bismuth colloidal pectin 300 mg, amoxicillin 1000 mg, and minocycline 100 mg, all given twice daily. Among a total of 101 H. pylori isolates, tetracycline resistance was 3.0%, whereas minocycline resistance was nil. A total of 114 patients (treatment-naïve/experienced, 72/42) received the minocycline/amoxicillin-based BQT. The overall intention-to-treat (ITT) and per protocol (PP) eradication rates were 94.7% (108/114) and 97.3% (108/111), respectively. The ITT and PP eradication rates were 91.7% (66/72) and 95.7% (66/69) among the treatment-naïve patients, and both were 100.0% among the treatment-experienced patients. No serious adverse event was recorded. This pilot study suggests that minocycline/amoxicillin-based BQT is an excellent therapy for H. pylori eradication.